INFLUENCIA DEL DETERIORO DEL CEPILLO DENTAL SOBRE LA HIGIENE BUCAL DE ESCOLARES (2012)
Objective: to determine the effect of the toothbrush wear on oral hygiene in students enrolled in second grade at Concentración Yira Castro evaluated during the second period of 2009.Methods: an observational following study was done with a 59 school children aged 6 to 9 years old cohort. The variables were: sociodemographic aspects, functional motor ability, attitude of the child at the time of brushing, oral hygiene-related with the toothbrush wear and the amount of dental plaque. The statistical analysis plan included to calculate the summary measures. The analysis to compare the oral hygienic and the toothbrush wear in each control a repeated ANOVA test was applied. The oral hygienic and toothbrush wear correlate was studied with Spearman correlate coefficient. The association the oral hygienic with other variables was evaluated with Chi square, Fisher exact and the t Student test, and the survival analysis for toothbrush wear was done. For all tests, p<0.05 was considered statistically significant.Results: the average for dental plaque representing a bad to regular oral hygiene were (2.6 ± 0.3 y 1.7 ±0.4) y de (2.2 ± 0.6 y 1.5 ± 0.5) before and after brushing by the first and last control, respectively. There was statistically significant differences between tootbrushing before and after in all the four controls. It was showed low levels of correlations between the level of oral hygiene and the toothbrush wear which ranged from -0.04 to 0.35.Conclusions: there was no relationship between the toothbrush wear and the oral hygiene level. The problem related to oral hygienic in the students that were including in this study was a bad tooth brushing technique.